(untitled) (World Bulletin of Management and Law, 2022)
The digitalization is entering into every direction by changing human being’s position. Even the traditional paper currencies are becoming electronic. On this article, we will discuss the effect of digitalization on inheritance procedure and policy, the ways of regulating these legal relations. Social networks policy and European Union practice is already concerned some approaches to regulate this process but did not cover up it fully. However, the Republic of Uzbekistan is trying to establish normative acts of digital inheritance. The article also concerns suggestions of digitalization in inheritance law process in Uzbekistan by adopting several normative acts and ways regulating this process